'We actually created a good mood!': metalinguistic and literary engagement through collaborative translation in the secondary classroom. Issue 3 (3rd July 2021) - Beauvais, Clémentine; Ryland, Charlotte
ABSTRACT: This paper presents findings from observations of literary translation workshops with secondary-school MFL pupils, revolving around a literary translation from L2 to L1 which does not require pre-existing language skills in the L2. Our research questions were: what skills do pupils mobilise when they work in groups on a literary translation? What can we say of the pupils' engagement and motivation? The data shows that pupils mobilise three categories of skills: metalinguistic, linguistic, and literary. Our first contention is that metalinguistic reflection feeds into both linguistic and literary aspects of the exercise and contributes to binding them together. The pupils displayed engagement most intensely when finding a translational 'solution' with expressive potential (that 'sounds good'). Their motivation was maintained through oral performance: pupils engage in vast amounts of vocalisation. We suggest that the spontaneous performative aspects of literary translation workshops help pupils process text, negotiate the linguistic territory across source and target language, and evaluate the aesthetic potential of their writing. Our second contention, therefore, is that translation in schools should maximise possibilities for moments of performance, opting for literary texts with strong expressive quality and potential for vocalisation.